Giving Operational Semantics to Multi-Context Systems Using DEVS - Pilotti, Pablo (2010)
Multi-context systems have proven to be a powerful tool for formalizing complex logical problems in Artificial Intelligence, providing a flexible framework that allows the definition of different formal components and their interrelationships. Several MCS applications are oriented towards multiagent systems, in which several asynchronous tasks (inferences, messaging, etc.) are carried out. In spite of their expressive power, MCS lack of an appropriate mechanism to capture their underlying operational semantics when they are used to provide a computational model for such systems. This paper presents a first approach to give operational semantics to MCS using Discrete Event System Specification (DEVS), a modular and hierarchical formalism for modeling, simulating and analyzing discrete event systems. We show that our proposal provides a flexible model for capturing several features of an agent’s reasoning process in an asynchronous setting.